Obstacles To Women's Political Work In Contemporary Iraqi Political Systems (1925-2018) Historical-Political Study (Journal of the College of Basic Education, 2024)
The participation of Iraqi women in political life is an urgent necessity and a social demand aimed at the advancement of society. It is also linked to all economic, social, political and cultural changes and transformations in society, and to their political role, and the interrelated relationship between women and men. Women in Arab countries in general, and in Iraq in particular, face great difficulties in the process of political participation, especially in candidacy and election, in accessing legislative authority, and in participating with men in making decisions that shape the state’s policy.The obstacles that stand in the way of women’s political ambition and participation in the essence of the political process represented by parliamentary elections is the title of the research, which included two chapters and a number of sections. The first chapter shed light on the practical journey of Iraqi women after the establishment of the Iraqi Kingdom, which was a parliamentary constitutional kingdom in which decision-making was limited to men. Without including womenWhile the second chapter dealt with the entry of women into the political process starting in 1980 and their participation in the elections for the Iraqi National Council, and their obtaining (16) seats in the National Council, but it was not at the level of ambition and did not relate to democratic foundations. Al-Fadl also included the state of the change that he underwent. The political system in Iraq after 2003 and the negatives and positives that accompanied this stage of dangerous developments in Iraqi society represented by the issuance of the Iraqi Constitution of 2005, which paved the way for women to participate more broadly in their entry into the political process.